Social difference and relational coaching: finding new freedoms in working with identity - Tawadros, Tammy; de Haan, Erik; Birch, David (Frontiers in Psychology, 2024)
In this article we explore some of the processes involved in dealing with Social Difference (SD) in coaching. Using examples from our own practice, we consider several factors, including the identity work involved in navigating the experience of SD in one-to-one coaching. Dealing with experiences of difference, including social class, gender, race, ability, and sexuality can invoke complicated and powerful feelings. Feelings of guilt, shame, anger, and isolation may cause impasses and ruptures in the coaching relationship. The article also sets out to test two hypotheses. Namely that working with questions of SD can enrich coaching if the Working Alliance (WA) is experienced as positive, and that issues of SD are better managed if they are discussed explicitly. We draw on social constructionist conceptions of identity, together with Rothberg's work on the implicated subject, to facilitate inquiry into SD and identity for ourselves as coaches, as well as for our coachees. This is the work of re-examining ourselves, re-thinking who we are, and moving beyond the unwanted aspects of the self which may provoke existential feelings of guilt, shame, anger, and isolation, as accumulated through or aggravated by the current and historical woundings of oppression and social injustice. Our research tells us that it is by facing into the complicated emotions engendered by SD, that we can begin to embrace what we psychically and socially 'disown'. We suggest that by recognising our implicated selves, we may become better equipped psychologically, to be more sensitive and responsive to the impact that SD has on individuals, groups, and organisations. We discuss the ways in which a relational stance in coaching can help to provide a secure holding environment for critical and reflexive inquiry into SD, identity and the selves we enact. We conclude that a relational and implicated approach in coaching provides a wider perspective and extends the critical capacity of leaders to look within themselves and into their challenges with more congruence and ethical maturity.